The quagmire of philosophical standpoints (paradigms) in management research - Mohammed Kamil, Naail (Editura Lumen, 2011)
In conducting management research, the researcher’s stance of ontology and epistemology in the contribution of knowledge is paramount. The acknowledgement of such stance is imperative as it may have inherent effects from how a research is conducted to how findings are reported and evaluated. This exploratory study attempts to provide a brief discussion of the philosophical standpoints (paradigms) characterized in management research. The discussion covered the two extremes; from the early modernism (positivism school of thought) to the other extreme of social constructionism. Other schools of varying standpoints of ontology and epistemology occur between these extremes. For individual schools of thought (paradigms), the ontological status of social reality, the ontological status of human behavior and the epistemological status, has been discussed.